Formulation Development and Physicochemical Characterization of Floating Microballoons of Propranolol Hydrochloride - Yadav, Akash; Kumar Jain, Dinesh (Asian Journal of Chemistry, 2012)
Microballoons floatable on JPXIII No.1 solution were developed as a dosage form capable of floating in the stomach. Microballoons were prepared by the emulsion solvent diffusion method using enteric acrylic polymers with drug in a mixture of dichloromethane and ethanol. It was found that preparation temperature determined the formation of cavity inside the microballoons and the surface smoothness, determining the floatability and the drug release rate of the microballoon. The correlation between the buoyancy of microballoons and their physical properties, i.e. apparent density and roundness of microballoons were elucidated. The drug loading efficiency of microballoons with various types of drug was investigated and correlated to the distribution coefficient of drug between dichloromethane and water. The optimum loading amount of propranolol hydrochloride in the microballoons was found to impart ideal floatable properties to the microballoons.